Death Anxiety in Nurses Working in the Intensive Care Units for COVID-19 Patients in Hospitals Affiliated to Tehran University of Medical Sciences - Akram Salamat; Zahra Siahmansour khorin; Zahra Abbasi; Leila Ghanbari; Maryam Khalili (Iran University of Medical Sciences, 2023)
Background & Aims Due to the effects of COVID-9 , health care workers, including nurses, faced many psychological challenges, including death anxiety. This study aims to determine the death anxiety level of nurses working in the intensive care units (ICUs) for COVID-19 patients in hospitals affiliated to Tehran University of Medical Sciences in 2020. Materials & Methods This is a descriptive cross-sectional study that was conducted on 179 nurses working in the ICUs for COVID-19 patients in two hospitals located in Tehran and Qom cities. Continuous sampling method was used for their selection. Data collection was done using a demographic form and Templer's 15-item death anxiety scale.  Results The mean death anxiety score of nurses was 8.74±2.007 out of 15, which is higher than the median score (i.e., 7.5). The results of one-way analysis of variance showed that the death anxiety score was significantly different between nurses only in terms of age (P=0.000). Tukey's post hoc test showed that the mean DAS score in nurses aged 30-39 was lower than in nurses aged ≥40 years and <30 years. There was no statistically significant difference in death anxiety between nurses in terms of other demographic factors (P>0.05).  Conclusion The nurses working in ICUs experienced a high level of death anxiety during the COVID-19 in Iran. It is necessary that the policy makers and educational, medical or hospital managers develop educational and interventional programs including online in-service programs or educational booklets to help nurses overcome the COVID-19-related conditions.